Dupilumab Efficacy in Patients with Type 2 Asthma with and without Elevated Blood Neutrophils - Eugene R. Bleecker; Reynold A. Panettieri; Njira L. Lugogo; Jonathan Corren; Nadia Daizadeh; Juby A. Jacob-Nara; Yamo Deniz; Paul J. Rowe; Angela Khodzhayev; Xavier Soler; Thomas J. Ferro; Christopher N. Hansen (Journal of Immunology Research)
Introduction. Elevated neutrophil counts in blood, sputum, or lung have been associated with poor clinical outcomes and more severe disease in patients with type 2 asthma. In the phase 3 LIBERTY ASTHMA QUEST (NCT02414854), add-on dupilumab 200 and 300 mg every 2 weeks compared with matched placebo significantly reduced severe asthma exacerbations and improved forced expiratory volume in 1 s (FEV1) in patients with uncontrolled, moderate-to-severe asthma. This post hoc analysis explored the efficacy of dupilumab in patients with type 2 asthma enrolled in QUEST with or without elevated blood neutrophil counts. Methods. Annualized severe exacerbation rates during the 52-week treatment period and least-squares mean change from baseline in FEV1 over time were evaluated for patients with elevated type 2 biomarkers at baseline (blood eosinophils ≥ 150 cells/µL or fractional exhaled nitric oxide (FeNO) ≥ 20 ppb; and eosinophils ≥ 300 cells/µL or FeNO ≥ 50 ppb) and low (<4,000 cells/µL) or high (≥4,000 cells/µL) neutrophil counts. Results. Dupilumab significantly reduced annualized severe exacerbation rates compared with placebo during the 52-week treatment period in patients with elevated type 2 biomarkers, irrespective of baseline neutrophil count (P<0.0001 for all comparisons). Significant improvements in FEV1 versus placebo were observed as early as Week 2 and over the 52-week treatment period, irrespective of baseline neutrophil count (P<0.001 for all comparisons). Safety findings were similar across all subgroups, regardless of neutrophil counts at baseline. Conclusions. Dupilumab treatment significantly reduced annualized severe exacerbation rates and improved lung function in patients with uncontrolled, moderate-to-severe, type 2 asthma, irrespective of baseline blood neutrophil count. This trial is registered with NCT02414854.